Upaya Adaptasi dan Mitigasi Perubahan Iklim di Pesisir Pantai Payum - Tutik Yuliatun; Kristina Uskenat; Andi Reski (Prima Abdika: Jurnal Pengabdian Masyarakat, 2026)
Climate change has had a significant impact on coastal areas, including Payum Beach in Merauke, South Papua. Rising sea levels, increased storm frequency, and coastal erosion are real threats endangering ecosystems and the lives of coastal communities. This community service activity aims to provide an optimal understanding of the importance of climate change mitigation efforts through the tangible implementation of mangrove planting. This activity was carried out from May 9, 2025, to May 27, 2025, on the shores of Payum Beach. The activity was conducted in three stages: planning, implementation, and monitoring. Identified adaptation and mitigation efforts include planting mangrove vegetation and educating the local community about climate change risks. The study results show that collaboration between the service team and the community is key to this program's success. However, challenges such as a lack of funding and weak coordination among parties remain major obstacles. An integrated, ecosystem-based, and participatory approach is needed to strengthen the resilience of coastal areas to the impacts of climate change in the future.